# C++ Program for Sum of squares of first n natural numbers

Given a positive integer N. The task is to find 12 + 22 + 32 + ….. + N2.

Examples:

```Input : N = 4
Output : 30
12 + 22 + 32 + 42
= 1 + 4 + 9 + 16
= 30

Iput : N = 5
Output : 55
```

## Recommended: Please try your approach on {IDE} first, before moving on to the solution.

Method 1: O(N) The idea is to run a loop from 1 to n and for each i, 1 <= i <= n, find i2 to sum.

 `// CPP Program to find sum of square of first n natural numbers ` `#include ` `using` `namespace` `std; ` ` `  `// Return the sum of the square  ` `// of first n natural numbers ` `int` `squaresum(``int` `n) ` `{ ` `    ``// Iterate i from 1 and n ` `    ``// finding square of i and add to sum. ` `    ``int` `sum = 0; ` `    ``for` `(``int` `i = 1; i <= n; i++) ` `        ``sum += (i * i); ` `    ``return` `sum; ` `} ` ` `  `// Driven Program ` `int` `main() ` `{ ` `    ``int` `n = 4; ` `    ``cout << squaresum(n) << endl; ` `    ``return` `0; ` `} `

Output:

```30
```

Method 2: O(1) Proof:

```We know,
(k + 1)3 = k3 + 3 * k2 + 3 * k + 1
We can write the above identity for k from 1 to n:
23 = 13 + 3 * 12 + 3 * 1 + 1 ......... (1)
33 = 23 + 3 * 22 + 3 * 2 + 1 ......... (2)
43 = 33 + 3 * 32 + 3 * 3 + 1 ......... (3)
53 = 43 + 3 * 42 + 3 * 4 + 1 ......... (4)
...
n3 = (n - 1)3 + 3 * (n - 1)2 + 3 * (n - 1) + 1 ......... (n - 1)
(n + 1)3 = n3 + 3 * n2 + 3 * n + 1 ......... (n)

Putting equation (n - 1) in equation n,
(n + 1)3 = (n - 1)3 + 3 * (n - 1)2 + 3 * (n - 1) + 1 + 3 * n2 + 3 * n + 1
= (n - 1)3 + 3 * (n2 + (n - 1)2) + 3 * ( n + (n - 1) ) + 1 + 1

By putting all equation, we get
(n + 1)3 = 13 + 3 * Σ k2 + 3 * Σ k + Σ 1
n3 + 3 * n2 + 3 * n + 1 = 1 + 3 * Σ k2 + 3 * (n * (n + 1))/2 + n
n3 + 3 * n2 + 3 * n = 3 * Σ k2 + 3 * (n * (n + 1))/2 + n
n3 + 3 * n2 + 2 * n - 3 * (n * (n + 1))/2 = 3 * Σ k2
n * (n2 + 3 * n + 2) - 3 * (n * (n + 1))/2 = 3 * Σ k2
n * (n + 1) * (n + 2) - 3 * (n * (n + 1))/2 = 3 * Σ k2
n * (n + 1) * (n + 2 - 3/2) = 3 * Σ k2
n * (n + 1) * (2 * n + 1)/2  = 3 * Σ k2
n * (n + 1) * (2 * n + 1)/6  = Σ k2
```

 `// CPP Program to find sum ` `// of square of first n ` `// natural numbers ` `#include ` `using` `namespace` `std; ` ` `  `// Return the sum of square of ` `// first n natural numbers ` `int` `squaresum(``int` `n) ` `{ ` `    ``return` `(n * (n + 1) * (2 * n + 1)) / 6; ` `} ` ` `  `// Driven Program ` `int` `main() ` `{ ` `    ``int` `n = 4; ` `    ``cout << squaresum(n) << endl; ` `    ``return` `0; ` `} `

Output:

```30
```

Avoiding early overflow:
For large n, the value of (n * (n + 1) * (2 * n + 1)) would overflow. We can avoid overflow up to some extent using the fact that n*(n+1) must be divisible by 2.

 `// CPP Program to find sum of square of first ` `// n natural numbers. This program avoids ` `// overflow upto some extent for large value ` `// of n. ` `#include ` `using` `namespace` `std; ` ` `  `// Return the sum of square of first n natural ` `// numbers ` `int` `squaresum(``int` `n) ` `{ ` `    ``return` `(n * (n + 1) / 2) * (2 * n + 1) / 3; ` `} ` ` `  `// Driven Program ` `int` `main() ` `{ ` `    ``int` `n = 4; ` `    ``cout << squaresum(n) << endl; ` `    ``return` `0; ` `} `

Output:

```30
```

Please refer complete article on Sum of squares of first n natural numbers for more details!

My Personal Notes arrow_drop_up
Article Tags :

Be the First to upvote.

Please write to us at contribute@geeksforgeeks.org to report any issue with the above content.